The Emergence of the Distinction between Complete and Incomplete Causes from Avicenna to al-Abharī - Muhammet Fatih Kılıç (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
This study explores the historical stages of the development of the distinction between complete and incomplete causes (al-ʿilla al-tāmma and al-ʿilla al-nāqisa) that first emerged during the thirteenth century and was frequently used thereafter in philosophical and theological writings. I will analyze the evolution of one specific passage in Avicenna’s (d. 428/1037) Ishārāt, namely, III.V.8, in the context of causal sufficiency during the post-classical era of Islamic thought. Abū al-Barakāt al-Baghdādī (d. 547/1152), Suhrawardī (d. 587/1191), and Fakhr al-Dīn al-Rāzī (d. 606/1210), all of whom provided the first examples of the concept of complete cause, offered an important notion related to this distinction. Moreover, we can read al-Rāzī’s attempt to define it with regard to its function in his al-Maṭālib as an attempt to include the divine will within the causal processes. However, as these scholars made no clear distinction between these two causes, they presented no clear definition of the former. The first clear distinctions, provided by Athīr al-Dīn al-Abharī (d. 663/1265) and Najm al-Dīn al-Kātibī (d. 675/1277), occupied an essential place in the chapters of causality found within philosophical and theological texts written after the thirteenth century.